EMPLACEMENT DEPTHS OF THE LATE PALEOZOIC - MESOZOIC GRANITOID INTRUSIONS FROM THE NORTHERN NORTH CHINA BLOCK AND THEIR TECTONIC IMPLICATIONS - Zhang S.H.; Zhao Y.; Liu J.; Hu J.M.; Chen Z.L.; Li M.; Pei J.L.; Chen Z.Y.; Zhou J.X. (My University, 2007)
Application of aluminum-in-hornblende geobarometry to different granitoid intrusions from the northern part (the Inner Mongolian Paleo-uplift, IMPU) and the southern part (Yanshan fold-and-thrust belt) of the northern margin of North China block (NCB) provides much useful information on the uplift and exhumation processes of this area since the Late Paleozoic. Emplacement depths estimated from aluminum-in-hornblende geobarometry indicate that the differential uplift and exhumation between the IMPU and the Yanshan fold-and-thrust belt was distinct during the Late Paleozoic to Early Mesozoic, but not distinct since the Early Jurassic. The exhumation of the basement crystalline rocks and absence of the Meso-Neoproterozoic and Paleozoic sedimentary rocks in the IMPU and widely distribution of the Meso-Neoproterozoic and Paleozoic sedimentary rocks in the Yanshan fold-and-thrust belt are likely a result of these strong differential uplift and exhumation during the Late Paleozoic to Early Mesozoic. The strong uplift and exhumation of the IMPU were achieved during the Late Paleozoic to Early Mesozoic, and its central-eastern part likely underwent more uplift and exhumation than its eastern part. The strong uplift and exhumation of the IMPU and the differential uplift and exhumation between the IMPU and the Yanshan fold and thrust belt were likely related to the southward subduction of the Paleo-Asian oceanic plate beneath the NCB, collision between the Mongolian are terranes and the NCB, and movement of the regional faults such as the Pingquan-Gubeikou-Chicheng-Shangyi fault and the Chifeng-Weichang-Duolun fault during this period. The strong uplift and exhumation of the Yanshan fold-and-thrust has been achieved since the Late Jurassic-Early Cretaceous. Since this period, both southern and northern parts of the northern NCB have undergone distinct uplift and exhumation, which was likely related to the strong crustal extension of the northern NCB and the eastern China.
Keywords: ALUMINUM-IN-HORNBLENDE GEOBAROMETRY; DIFFERENTIAL UPLIFT AND EXHUMATION; EMPLACEMENT DEPTH OF PLUTON; INNER MONGOLIA PALEO-UPLIFT; NORTH CHINA BLOCK; YANSHAN FOLD AND THRUST BELT; Mesozoic::Jurassic; Мезозой::Юрская